Differential Properties of the Synaptogenic Activities of the Neurexin Ligands Neuroligin1 and LRRTM2 - Dagar, Sushma; Gottmann, Kurt (Frontiers in Molecular Neuroscience, 2019)
Synaptic cell adhesion molecules are well established to exhibit synaptogenic activity when overexpressed in target cells, indicating that they are involved in formation and functional maturation of synapses. The postsynaptic adhesion proteins Neuroligin1 and LRRTM2 both induce synaptic vesicle clusters in presynaptic axons in vitro by transsynaptically interacting with neurexins. Although the synaptogenic activity of Neuroligin1 has been well characterized, the properties of the synaptogenic activities of other synaptic adhesion molecules are largely unknown. In this paper, we now compared characteristics of the synaptogenic activities of Neuroligin1 and LRRTM2 upon overexpression in cultured mouse cortical neurons. Individual cortical neurons were transfected with Neuroligin1 and LRRTM2 expression plasmids, respectively and synaptic vesicle clustering in contacting axons was examined by immunostaining for the vesicle membrane protein VAMP2. In immature neurons at 6-7 days in vitro (DIV) both Neuroligin1 and LRRTM2 exhibited strong synaptogenic activity. However, upon further neuronal differentiation only LRRTM2 retained significant synaptogenic activity at 12-13 DIV. Most interestingly, the synaptogenic activity of Neuroligin1 was strongly dependent on the expression and function of the synaptic adhesion molecule N-cadherin in immature neurons. In contrast, the synaptogenic activity of LRRTM2 was independent on N-cadherin expression and function in both immature and more mature neurons (14-15 DIV). Taken together, our results with overexpression in cultured cortical neurons revealed striking differences in the properties of the synaptogenic activities of Neuroligin1 and LRRTM2, although both transsynaptically interact with presynaptic neurexins.